2009
DOI: 10.1111/j.1365-2745.2009.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Do facilitative interactions increase species richness at the entire community level?

Abstract: Summary 1.Although the consequences of facilitation at individual and population levels are well known, the community-level consequences of these processes have received much less attention. In particular, the importance of facilitation in determining richness at the entire community level has seldom been evaluated. 2. In this study, we sampled 11 alpine plant communities along the southern Andes in South America, spanning from tropical (25°S) to sub-antarctic latitudes (55°S). Plant communities were dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
262
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(282 citation statements)
references
References 58 publications
14
262
1
5
Order By: Relevance
“…That is to say, the growth of A. tamarense was controlled by the bacteria and the bacteria were controlled by Ochromonas sp. In general, the results of species interactions are the final outcome of a balance between negative and positive interactions, and consideration of the role played by species interactions in communities could contribute to maintaining community diversity and stability (Mulder et al, 2001;Cardinale et al, 2002;Butterfield, 2009;Cavieres and Badano, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…That is to say, the growth of A. tamarense was controlled by the bacteria and the bacteria were controlled by Ochromonas sp. In general, the results of species interactions are the final outcome of a balance between negative and positive interactions, and consideration of the role played by species interactions in communities could contribute to maintaining community diversity and stability (Mulder et al, 2001;Cardinale et al, 2002;Butterfield, 2009;Cavieres and Badano, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Cavieres and Badano 2009). They have shown that dominant cushions increased species richness at the site scale even in cases where they did not have a significant local effect on average species richness and diversity .…”
Section: Site Scalementioning
confidence: 99%
“…Competition (Dybzinski & Tilman 2007;Weigelt et al 2007) and facilitation (Bruno, Stachowicz, & Bertness 2003;Brooker et al 2008) can act simultaneously and interact in complex ways in structuring communities, and both mechanisms have been reported to explain species coexistence (Cavieres & Badano 2009;Wright 2002). Whereas competition has been proposed to be a major structuring force in less severe environments, facilitation tends to increase in importance in harsh environments (Bertness & Callaway 1994;Callaway et al 2002;Maestre, Callaway, Valladares, & Lortie 2009), where nurse plants (Padilla & Pugnaire 2006) improve environmental conditions for target plants through shading, ameliorating temperature extremes, changing soil properties, and increasing resource availability (Callaway 1995).…”
Section: Introductionmentioning
confidence: 99%